2012
DOI: 10.1055/s-0032-1321491
|View full text |Cite
|
Sign up to set email alerts
|

Quality in Molecular Biology Testing for Inherited Thrombophilia Disorders

Abstract: As the understanding of the genetic basis of the inherited thrombophilias has increased over recent years, their routine diagnostic genetic analysis has also matured. This review considers methods used to test for the factor V (F5) Leiden mutation and prothrombin 20210A (F2 c.*97G>A) allele, and analysis of the SERPINC1, PROC, and PROS1 genes in cases of antithrombin, protein C (PC), and protein S (PS) deficiency, respectively. Issues relating to quality are explored, highlighting where analytical and sample h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…47,48 None of the population group had large dosage mutations. A total of 16 novel mutations were identified in this study, two in PROC, seven in PROS1, and seven in SERPINC1 (Table 1).…”
Section: © F E R R a T A S T O R T I F O U N D A T I O Nmentioning
confidence: 99%
See 2 more Smart Citations
“…47,48 None of the population group had large dosage mutations. A total of 16 novel mutations were identified in this study, two in PROC, seven in PROS1, and seven in SERPINC1 (Table 1).…”
Section: © F E R R a T A S T O R T I F O U N D A T I O Nmentioning
confidence: 99%
“…Large dosage mutations were frequent in AT deficiency and PS deficiency in our group of patients (18.2% in SERPINC1 and 14.3% in PROS1) (Figure 2), and they were more frequent than in previous studies (9.1% and 6.4%, respectively). 47, 48 Although we did not perform MLPA experiments for PROC, the number of cases with large dosage mutations causing PC deficiency would have been quite limited when considering the rarity of these mutations in PROC (0.6%). 47,48 None of the population group had large dosage mutations.…”
Section: © F E R R a T A S T O R T I F O U N D A T I O Nmentioning
confidence: 99%
See 1 more Smart Citation
“…Large deletions are reported to be 3-6% in these deficiencies (5). Cooper et al (23) revealed that large deletions make up between 7 and 10% of PS and AT mutations and only 1% of PC mutations. The rare occurrence of thrombosis and the wide range of factor activities impeded to define the standard values of "true healthy" children who develop no thromboembolism until the forties.…”
Section: Discussionmentioning
confidence: 99%
“…Second line assays are typically those designed to provide further insights into abnormalities of screening tests, or used to monitor more accurately some antithrombotic therapies, and thereby include clotting factors assays [27] , ristocetin-induced platelet agglutination and VWF antigen tests [28] , anticardiolipin (aCL) IgG and IgM, anti-β (2) glycoprotein I (anti-β (2) GPI) antibodies IgG and IgM and phospholipid-dependent coagulation assays [29,30] , platelet function tests such as Platelet Function Analyzer-100 (PFA-100) and aggregometry [31,32] , assays for heparin-induced thrombocytopenia [33,34] , additional tests for thrombophilia screening including resistance to activated protein C, antithrombin, proteins C and S, and genetic polymorphisms/mutations (e.g., prothrombin G20210A and factor V Leiden) [35,36] along with ecarin clotting time, chromogenic anti-factor Xa and dilute Russell viper venom time (dRVVT) for monitoring novel anticoagulants [37,38] . Both first and second line tests might be available to most clinical laboratories, whereas third line tests -which are intended to troubleshoot the most challenging conditions and encompass analyses such as VWF collagen binding, VWF ristocetin cofactor assay, VWF-FVIII binding assay, multimer and molecular analysis for the precise classification of VWD [39,40] , coagulation factors inhibitors testing [41,42] , analyses of rare thrombophilic mutations [43] , rare platelet functional disorders [44] , pharmacogenetics testing [45,46] -are occasionally used and typically available in specialized laboratories. Quality in laboratory diagnostics is irrecusable, since spurious results obtained on unsuitable specimens may negatively bias the clinical decision-making and jeopardize patient safety.…”
Section: Laboratory Hemostasismentioning
confidence: 99%